From Overseas to the Classroom: Lived Experiences of Selected Teachers Working Abroad Who Plan to Return to the Teaching Profession - Bolere, Brian (International Journal of Sustainability and Advanced Integrated Research, 2026)
This phenomenological study explored the lived experiences of overseas Filipino educators holding advanced degrees in education who are currently employed in positions not fully aligned with classroom teaching in Riyadh, Saudi Arabia, yet intend to return to the profession. Guided by a qualitative phenomenological design, the study involved ten purposively selected participants who were licensed teachers and doctorate degree holders working in non-teaching or partially aligned roles. Data were collected through semi-structured in-depth interviews and analyzed using Moustakas’ phenomenological method.Findings revealed four major themes. First, Professional Identity Tension and Vocational Persistence highlighted the enduring self-concept of participants as educators despite occupational displacement. Second, Economic Pragmatism and Migration Rationalization underscored the role of financial stability and family responsibility in shaping migration decisions. Third, Skill Enrichment and Reintegration Readiness emphasized the development of transferable competencies such as intercultural communication, adaptability, and leadership, which participants perceived as assets for future teaching practice. Fourth, Structural Barriers and Occupational Mismatch described systemic constraints, including credential recognition challenges and employment regulations, that limited access to aligned teaching roles in the host country.The essence of the phenomenon suggests that overseas employment among doctorate/master degree holders in education represents a strategic and adaptive phase rather than professional abandonment. Despite structural labor constraints, professional identity remains resilient, and reintegration aspirations are sustained. The study contributes to scholarship on teacher migration, professional identity reconstruction, and reintegration readiness, offering policy implications for structured return programs and strategic talent reintegration initiatives within the Philippine education system
Keywords: Professional Identity, Overseas Filipino Educators, Occupational Mismatch, Reintegration Readiness, Teacher Migration, Phenomenology